Insomnia Symptoms in Patients With Substance Use Disorders During Detoxification and Associated Clinical Features - Grau-López, Lara; Grau-López, Laia; Daigre, Constanza; Palma-Álvarez, Raúl Felipe; Martínez-Luna, Nieves; Ros-Cucurull, Elena; Ramos-Quiroga, Jose Antonio; Roncero, Carlos (Frontiers in Psychiatry, 2020)
Background: Insomnia is highly prevalent in patients with substance use disorders (SUD) and it has been related with worse addiction course. Insomnia during a hospital detoxification process has not been enough studied. This study aims to compare sociodemographic, clinical, and psychopathological characteristics of SUD patients undergoing a detoxification program, according to comorbidity with insomnia symptoms. Methodology: 481 patients were recruited, who received pharmacological and psychotherapeutic treatment for detoxification. They were evaluated by semi-structured interviews, standardized questionnaires and a specific sleep log. . A bivariate and multivariate analysis of the data was performed. Results: Insomnia was reported by 66.5% patients, being sleep-maintenance insomnia the most frequent issue, followed by early morning awakening and sleep-onset insomnia. Patients with alcohol use disorder and cannabis use disorder had higher prevalence of sleep-onset insomnia. Patients with cocaine and heroin use disorder had higher prevalence of sleep-maintenance insomnia. Independent factors that allowed identification of insomnia symptoms were being female (OR:3.43), polysubstance use (OR:2.85), comorbid anxiety disorder (OR:2.02), and prior admission for detoxification (OR:1.22). Conclusions: Insomnia symptoms are very prevalent in patients admitted for detoxification. The diagnosis and therapeutic strategies for the insomnia symptoms should be improved, especially in women, in patients with greater addiction severity and with anxiety disorders.